Why do we fail to fail Undergraduate Medical Students? A Perception of Ophthalmology Faculty - Sidrah Riaz, Shabana Choudhary, Zahid Kamal, Muhammad Tariq Khan, Umair Tariq Mirza, Khalid Mehmood, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective of study: To evaluate the ophthalmology faculty perspective on why they fail to fail undergraduate medical students. Place and duration: Medical colleges and universities of both public and private sectors, duration was three (3) months Study design: It was a cross sectional survey. Non-probability conventional non interventional sample was used. The data was analyzed by SPSS-25. Methods: Total 134 university examiners for undergraduate medical students from ophthalmology faculty were identified from the websites of both private and public sector medical universities and colleges of the Punjab, Pakistan. The ophthalmology faculty members with more than five years of experience as a faculty were included in the study. An online survey questionnaire was sent out through Google forms. The faculty members were given reminder twice. The responses are analyzed with SPSS-25. Results: Out of 134 ophthalmology examiners, 98 (73.13%) examiners responded to the questionnaire. Among the respondents, only 80 faculty members, 58 (72.5%) males and 22 (27.5%) females, with teaching experience of more than five years, are included in the data analysis. Fifty-four (55.10%) participants declared teaching experience of more than ten years while 26 (26.53%) had experience between five to ten years. Twenty-seven (33.75%) respondents had additional qualification in the field of medical education like certification, diploma, or master’s degree (CHPE or MHPE). Fifty-five respondents (68.75%) opted that a few unmerited students passed fourth professional medical university exam. Further, 47 (58.75%) respondents also agreed that they were failed to fail a few ineligible and inefficient undergraduate 4th year medical student while marking a viva voce interactive session, a mandatory section in practical examination, as an internal or external examiner, whereas 33 (41.25%) respondents disagreed with this statement. The top five reasons behind failure to fail, as identified by the respondents were poor assessment methods (50%), lenient examiners (37.5%), commendation by colleagues or administration (22.5%), irrelevant syllabus (12.5%) and pressure from college administration (10%). Mixed opinion regarding the standards of medical education in Pakistan was emerged, according to 45% participants “it is improving”, while 55% had opinion “it is deteriorating”. The top four suggestions opted by the participants regarding improvement in medical students’ assessment to avoid fail to fail phenomena, were “teachers should be more experienced” (60%), “strictly following the criteria of 75% mandatory attendance set by university while sending students admission for university exam” (50%), “revision of admission criteria while selecting first year medical students” (25%) and “adoption of honest policy by administration while selecting students for admission in medical college” (10%). About 60 (75%) examiners felt the need to revise ophthalmology syllabus for under graduates. Conclusion: Being a medical teacher and an examiner is considered as an honour as well as a great responsibility because their students are going to be the future serving doctors, dealing with human life. An unsafe physician or surgeons is neither desirable for doctors’ community nor for the society. Examiners should be more trained, more experienced, and able to assess the failing student if he or she is inadequate, deficient, or not meeting the required standard without any bias. The formative assessment should be dependable, reliable, and rigid as compared to summative assessment and failing a student should be considered as providing them a second chance for their improvement rather than producing an inadequate or incompetent doctor. The standardized admission criteria and merit policies need to be followed. The ophthalmology syllabus should be revised as it needs to be more community oriented and precise.